In Which Exchange Rate Models Do Forecasters Trust? - Lee, Jaewoo (IMF Working Papers; Working Paper ;, 2011)
Using survey data of market expectations, we ask which popular exchange rate models appear to be consistent with expectation formation of market forecasters. Exchange rate expectations are found to be correlated with inflation differentials and productivity differentials, indicating that the relative PPP and Balassa-Samuelson effect are common inputs into expectation formation of market forecasters.